Gud og det givne: om diskursiv teisme - Andersen, Svend (Dansk teologisk tidsskrift, 2017)
Resumé Two important preconditions for the thinking of God in contemporary philosophy of religion are Kant’s critique of the ontological argument and Heidegger’s critique of so-called onto-theology. In both cases we find a critique of metaphysics and in both cases the concept of being or existence is central. Against this background, the article discusses the thinking about God in K.E. Løgstup and Jean-Luc Marion, who both relate to Heidegger’s thought and to phenomenology. Other contributions are included, viz. Johannes Sløk’s and Niels Grønkjær’s. The main thesis is that there can be no ‘unbroken’ discourse about God in the context of a Heideggerian Seinsdenken. Language is a necessary intermediate: the transition from the sphere of being to God as a person presupposes linguistic discourse. Such a discursive theism is not vulnerable to the contemporary critique of metaphysics.